Art Practices in the Migration Society: Transcultural Strategies in Action at Brunnenpassage in Vienna - Wiederhold-Daryanavard, Anne; Wiederhold, Anne; Pilic, Ivana (transcript, 2021)
The established cultural sector is facing a paradigm shift. At the center of this change is the demand to do justice to the diversity of the population. The handbook opens up strategies for implementing art practices that are critical of discrimination, and for reaching new dialogue groups. Successes in partnerships with unequal cultural institutions are analyzed, and concrete strategies for action are shown on the basis of eleven documented productions. Starting point are the insights from the artistic practice in Brunnenpassage Vienna, founded in 2007. The handbook sets practice-relevant impulses for cultural workers, artists, and cultural policy-makers.